Teaching Russian to Non-Native Speaking Students in the Multicultural Space of Russian and Moldova Universities - N. D. Afanasieva; M. A. Volkova; E. I. Tsymbalyuk (Высшее образование в России)
The article gives a comparative analysis of the factors promoting an increase of interest in learning Russian on the part of non-native speaking students. The research is based on the survey of 225 students carried out at MGIMO-University and Chisinau State Pedagogical University (Moldova). The authors revealed linguo-didactic and sociocultural factors defining students’ choice of language of communication at the university and promoting the building of cognitive interest to learning Russian and forming intercultural competence. The research has shown that 1) the foreign bachelor’s and master’s students have clear goals in learning Russian; 2) the majority of students express an apparent interest in learning Russian; 3) most of students are interested in receiving skills in professional communication in Russian. The professional training of specialists in international relations implies knowing of several languages, the ability to work in multicultural environment, the readiness to effective cross-cultural communication. The research showed that it is necessary to make adjustments in the educational environment and the content of educational programmes based on the labour market demands.